BchY-Based Degenerate Primers Target All Types of Anoxygenic Photosynthetic Bacteria in a Single PCR - Yutin, Natalya (American Society for Microbiology (ASM), 2009)
To detect anoxygenic bacteria containing either type 1 or type 2 photosynthetic reaction centers in a single PCR, we designed a degenerate primer set based on the bchY gene. The new primers were validated in silico using the GenBank nucleotide database as well as by PCR on pure strains and environmental DNA.